THE ROLE OF GOVERNMENT AND INFRASTRUCTURE IN INCREASING TOURIST INTEREST IN KERINCI REGENCY: A SWOT ANALYSIS: GAMPO HARYONO - Haryono, Gampo (Qawwam : The Leader's Writing, 2024)
This study examines the role of government and infrastructure in increasing tourist interest in Kerinci Regency using the SWOT analysis method. Kerinci Regency has great tourism with various natural attractions, but requires further development. further development. The role of local government includes the preparation of a tourism master plan, budget allocation, ease of licensing, promotion, and empowerment. plan, budget allocation, ease of licensing, promotion, and community empowerment. community. Infrastructure assessment includes accessibility, accommodation, supporting facilities, utilities, and tourism facilities and infrastructure. supporting facilities, utilities, and tourism facilities and infrastructure. SWOT was used to identify internal and external factors that influence tourism development in Kerinci Regency. The results of the research are expected to provide the right strategy to increase tourist interest and tourists and encourage regional economic growth.